Can the Media Discipline Chinese Firms' Pollution Behaviors? The Mediating Effects of the Public and Government. (September 2016) - Tang, Zhi; Tang, Jintong
Extant stakeholder studies posit that the media have a direct impact on firms' pollution behaviors. By integrating agenda-setting theory with the stakeholder framework, we propose the media exert an influence on firms' pollution behaviors through two primary stakeholders: the government and the public. Longitudinal archival data collected from Chinese newspapers in 2009 indicate that the government tends to take actions upon the official newspaper reports, while the public acts upon the reports from commercialized papers. Both the government's and the public's actions can prompt the firm to provide solutions to its pollution problems. In addition, the government's actions mediate the relationship between official media coverage and firm solutions, and the public's actions mediate the link between commercialized media coverage and firm solutions.